Factors affecting the efficiency of the use of material resources in the enterprise and ways to increase it - Mykytyuk, Vitalii; Flys, Viktor (Herald of Economics, 2024)
Introduction. In the conditions of the war and the post-war reconstruction of the economy of Ukraine, the main source of modernization transformations of the domestic industry is the intensification of production, the saving of material and other types of economic resources, and the improvement of the efficiency of the use of the accumulated resource potential. The dynamics of the efficiency of material consumption and the level of material intensity in the production process are formed under the influence of exogenous and endogenous factors, taking into account the innovative components of standardizing the costs of material resources at the enterprise.The purpose of the study is to generalize and develop scientific and practical recommendations for increasing the efficiency of the use of material resources and finding reserves for reducing the material intensity of the company’s products.Research methods. In the research process, general scientific and special methods of cognition were used: the method of chain substitutions, absolute and relative differences, the index method, the integral method, the logarithmic method, the method of proportional division, the methods of economic-mathematical modeling, the optimization method, and the correlation-regression method.The results. The proposed system of indicators (empirical, modeling, control) will allow to detail the obtained results, to expand the understanding of the activities of the subjects of the enterprises in the direction of increasing the efficiency of the use of material resources, which will ensure a decrease in the material intensity and cost of industrial products in the process of their production. It was found that the current toolkit of analysis is limited in the application of methods for all types of structural-logical models and is characterized by high labor-intensiveness of mathematical functions and obtaining an economic interpretation, based on the performance of calculation actions taking into account the sequence of exogenous and endogenous factors of the model of the formation of the indicator of the effective use of material resources. It has been proven that the applied system of rationing the costs of material resources is based on the use of research-statistical, analytical- calculation and research-laboratory methods. It was established that the lack of the formation of regulatory costs is the absence of a factor accounting for the scientific and technical development of the enterprise, and possible losses (waste) of material resources in the production process.Prospects. Further research should be aimed at the implementation of a continuous process of increasing the efficiency of the use of material resources based on the development and application of a structural block diagram of the phased implementation of organizational and accounting operations with their systematization, which will significantly reduce the material intensity and cost of production.